2018
DOI: 10.3847/1538-4357/aab8fa
|View full text |Cite
|
Sign up to set email alerts
|

A Methane Extension to the Classical Habitable Zone

Abstract: The habitable zone (HZ) is the circumstellar region where standing bodies of liquid water could exist on the surface of a rocky planet. Conventional definitions assume that CO2 and H2O are the only greenhouse gases. The outer edge of this classical N2-CO2-H2O HZ extends out to nearly ~1.7 AU in our solar system, beyond which condensation and scattering by CO2 outstrip its greenhouse capacity. We use a single column radiative-convective climate model to assess the greenhouse effect of CH4 (10 -~100,000 ppm) on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 73 publications
2
75
0
Order By: Relevance
“…Hence the chemical feedback tends to cool the planets around late-type M dwarfs. This result is consistent with the study of Ramirez & Kaltenegger (2018) who found that for planets around late M dwarfs a CH 4 anti-greenhouse effect can shrink the HZ by about 20%. Our simulations do not include effects on the radiative transfer due to clouds and hazes.…”
Section: Resultssupporting
confidence: 93%
“…Hence the chemical feedback tends to cool the planets around late-type M dwarfs. This result is consistent with the study of Ramirez & Kaltenegger (2018) who found that for planets around late M dwarfs a CH 4 anti-greenhouse effect can shrink the HZ by about 20%. Our simulations do not include effects on the radiative transfer due to clouds and hazes.…”
Section: Resultssupporting
confidence: 93%
“…The single-column radiative-convective climate model has 55 thermal infrared and 38 solar wavelengths (Ramirez and Kaltenegger 2017;Ramirez and Kaltenegger 2018). Atmospheres are subdivided into 100 vertical logarithmically-spaced layers that reach ~1x10 -5 bar at the top of the atmosphere.…”
Section: The Single Column Radiative-convective Climate Modelmentioning
confidence: 99%
“…Over the years, many studies have continually revisited the limits of the habitable zone (HZ)(e.g. Dole 1964;Kasting et al 1993;Kopparapu et al 2013;Leconte et al 2013;Yang et al 2013;Ramirez and Kaltenegger 2014;Wolf and Toon 2014;Wolf and Toon 2015;Haqq-Misra et al 2016;Ramirez and Kaltenegger 2017;Bin et al 2018;Ramirez and Kaltenegger 2018), which is the circular region around a star (or multiple stars) where standing bodies of liquid water could exist on the surface of a rocky planet (Ramirez 2018a). Properly defining the habitable zone is and will likely remain (for the foreseeable future) an important scientific consideration because it is the main navigational tool that mission architectures use to find potentially habitable planets around other stars.…”
Section: Introductionmentioning
confidence: 99%
“…where T * = T eff − 5780, and S Sun is the stellar incident values at the HZ boundaries in our solar system. Table 2 (Ramirez & Kaltenegger 2018) shows the constants a, b, c, and S Sun needed to derive the stellar flux at the HZ limits valid for T eff between 2,600 to 10,000 K. The inner boundaries of the empirical HZ (recent Venus), as well as an alternative inner edge limit for 3D Global Climate models (3D; Leconte et al (2013)) and the outer limits (early Mars), are all included. The outer HZ limit in 3D and 1D models are consistent and therefore not given in separate columns in Table 2 (see e.g.…”
Section: As Shown Inmentioning
confidence: 99%